VERBA RESIPROKAL DALAM TEKS BERITA PADA SURAT KABAR HALUAN - Ramadhani, Bella Elisa; Juita, Novia (Universitas Negeri Padang, 2019)
The purpose of this study is to describe the process of forming reciprocal verbs and reciprocal verb meanings in the news text in the Haluan newspaper edition September-October 2018. This type of research is qualitative research with descriptive analysis method. The findings of this study are (1) the process of forming reciprocal verbs in the news text of the September-October 2018 there are seven, namelyn(1) prefixes (2) confixes, (3) models (D + ( R + meN)), (4) model (D + (R + meN - / - i)), (5) model (mutual + (D + meN - / - i)), (6) model (mutual + ( D + meN)), and (7) model (mutual + (D + meN - / - kan)); and (2) the reciprocal verb meanings in the news text of the September-October 2018 there are two, namely (1) the existence of relations between the two parties, and (2) the existence of